2021
DOI: 10.1038/s41467-020-20208-x
|View full text |Cite
|
Sign up to set email alerts
|

The ATM and ATR kinases regulate centrosome clustering and tumor recurrence by targeting KIFC1 phosphorylation

Abstract: Drug resistance and tumor recurrence are major challenges in cancer treatment. Cancer cells often display centrosome amplification. To maintain survival, cancer cells achieve bipolar division by clustering supernumerary centrosomes. Targeting centrosome clustering is therefore considered a promising therapeutic strategy. However, the regulatory mechanisms of centrosome clustering remain unclear. Here we report that KIFC1, a centrosome clustering regulator, is positively associated with tumor recurrence. Under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 52 publications
0
46
0
Order By: Relevance
“…CRC xenografts were established in 5-week-old female BALB/c nude mice purchased from the Institute of Zoology, Chinese Academy of Sciences, Shanghai. Tumor-bearing and the calculation of tumor volumes were performed as previously described [ 32 ]. Briefly, SHMT2-sh and control cells (3 × 10 6 ) were injected subcutaneously into the flanks of nude mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CRC xenografts were established in 5-week-old female BALB/c nude mice purchased from the Institute of Zoology, Chinese Academy of Sciences, Shanghai. Tumor-bearing and the calculation of tumor volumes were performed as previously described [ 32 ]. Briefly, SHMT2-sh and control cells (3 × 10 6 ) were injected subcutaneously into the flanks of nude mice.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was performed as previously described [ 32 ]. The intensity and extent of staining were evaluated independently by two pathologists blinded to the patient outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study has shown that KIFC1 phosphorylation induces chromosomal instability in breast cancer [ 31 ]. As shown in Figure 3 C, KIFC1 expression was increased in genomically unstable type BC in the IMvigor 210 study.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that KIFC1 is involved in cisplatin resistance in breast cancer [ 31 , 35 ]. Therefore, we analyzed the involvement of KIFC in cisplatin resistance in BC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation